Precision and Manipulation of Non-financial Information: The Curious Case of Environmental Liability - Aline Grahn (Abacus, 2020)
This paper develops a model showing how the environmental liability regime and the precision of the disclosed environmental performance indicator affect managers' incentives (1) to reduce actual pollution and (2) to manipulate the reported pollution. I assume a company with a separation of ownership and control which can be held liable for environmental damages and distinguish between a negligence regime and strict liability. The results suggest that if there is no manipulation but only a lack of precision of the disclosed environmental performance indicator, a negligence rule induces lower actual pollution levels than strict liability even though a negligence rule is considered to be more lenient. If managers are able to manipulate the disclosed environmental performance indicator, they will do so and actual pollution levels will generally increase. While manipulation makes it easier for shareholders to escape liability under a negligence regime, shareholders suffer from manipulation under strict liability due to higher actual pollution and higher expected damage compensation payments. Therefore, the manipulation level is higher under a negligence regime. My analysis contributes to the environmental performance and disclosure literature by showing that the liability regime is an important determinant affecting environmental reporting and actual pollution decisions.
Keywords: 330; Environmental performance; Environmental liability; Manipulation; Precision; Environmental pollution; Performance measurement; EPI; Environmental reporting